Effects of surface tension on the adhesive contact between a hard sphere and a soft substrate. (1st May 2016) - Long, Jianmin; Wang, Gangfeng; Feng, Xi-Qiao; Yu, Shouwen
Abstract: In the present paper, the adhesive contact between a rigid sphere and a compliant elastic substrate with surface tension is analyzed. Using the minimum potential energy principle and considering both the effects of surface tension and adhesion, explicit solutions are obtained for the contact radius and the indent depth for the case without external loading. It is found that surface tension evidently alters the pressure distribution in the contact region and tends to decrease both the contact radius and the indent depth. The present model establishes a bridge between the JKR model for adhesive contact problems and the Young-Laplace's law of surface tension.